Ginsenoside Rg3 Attenuates Lipopolysaccharide-Induced Acute Lung Injury via MerTK-Dependent Activation of the PI3K/AKT/mTOR Pathway - Yang, Jing; Li, Senyang; Wang, Luyao; Du, Fen; Zhou, Xiaoliu; Song, Qiqi; Zhao, Junlong; Fang, Rui (Frontiers in Pharmacology, 2018)
Acute lung injury (ALI) is a common clinical disease with high morbidity in both humans and animals. Ginsenoside Rg3, a type of traditional Chinese medicine extracted from ginseng, is widely used to cure many inflammation-related diseases. However, the specific molecular mechanism of the effects of ginsenoside Rg3 on inflammation has rarely been reported. Thus, we established a mouse model of lipopolysaccharide (LPS)-induced ALI to investigate the immune protective effects of ginsenoside Rg3 and explore its molecular mechanism. In wild type (WT) mice, we found that ginsenoside Rg3 treatment significantly mitigated pathological damages and reduced myeloperoxidase (MPO) activity as well as the production of pro-inflammatory cytokines tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6); furthermore, the production of anti-inflammatory mediators interleukin-10 (IL-10) and transforming growth factor-β (TGF-β), polarization of M2 macrophages and expression levels of the phosphorylation of phosphatidylinositol 3-hydroxy kinase (PI3K), protein kinase B (PKB, also known as AKT), mammalian target of rapamycin (mTOR) and Mer receptor tyrosine kinase (MerTK) were promoted. However, there were no significant differences with regards to the pathological damage, MPO levels, inflammatory cytokine levels, and protein expression levels of the phosphorylation of PI3K, AKT and mTOR between the LPS treatment group and ginsenoside Rg3 group in MerTK-/- mice. Taken together, the present study demonstrated that ginsenoside Rg3 could attenuate LPS-induced ALI by decreasing the levels of pro-inflammatory mediators and increasing the production of anti-inflammatory cytokines. These processes were mediated through MerTK-dependent activation of its downstream the PI3K/AKT/mTOR pathway. These findings identified a new site of the specific anti-inflammatory mechanism of ginsenoside Rg3.